1985
DOI: 10.1128/aac.27.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Activities of new quinoline derivatives against genital pathogens

Abstract: The in vitro activities of four quinoline carboxylic acids against 48 strains of Neisseria gonorrhoeae, 10 of Chlamydia trachomatis, and 32 of Ureaplasma urealyticum were compared. Ciprofloxacin was the most active against N. gonorrhoeae and C. trachomatis but had poor bactericidal activity against U. urealyticum, whereas ofloxacin showed the most bactericidal activity against U. urealyticum but was less active than ciprofloxacin against the two former pathogens. Norfloxacin and enoxacin were less active again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
16
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 23 publications
5
16
0
Order By: Relevance
“…Our study confirms the previous reports in which high activities of ciprofloxacin and ofloxacin were evaluated (1, 2, 10, 16, 18). The MICs of pipemidic acid, norfloxacin, and enoxacin were comparable to those found by other investigators (1,10). The MICs of minocycline were as favorable as those previously reported for doxycycline and tetracycline (2,10,16,18).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Our study confirms the previous reports in which high activities of ciprofloxacin and ofloxacin were evaluated (1, 2, 10, 16, 18). The MICs of pipemidic acid, norfloxacin, and enoxacin were comparable to those found by other investigators (1,10). The MICs of minocycline were as favorable as those previously reported for doxycycline and tetracycline (2,10,16,18).…”
supporting
confidence: 76%
“…Also, infertility resulting from salpingial obstruction is considered to be frequently caused by C. trachomatis (6). Several studies have shown that some kinds of quinolone, macrolide, and tetracycline drugs are effective against C. trachomatis in vitro (1,2,7,10,(15)(16)(17)(18). We evaluated the in vitro activities of three newly developed quinolone agents, T-3262, NY-198, and fleroxacin (AM-833, RO 23-6240), against 10 clinically isolated C. trachomatis strains and compared them with those of other quinolones and minocycline.…”
mentioning
confidence: 99%
“…A-56619 was the most active quinolone against both the lymphogranuloma venereum and occulogenital strains of C. trachomatis tested, having MICs eightfold lower than those of ciprofloxacin. The isolates were fully resistant to norfloxacin, as previously reported (1,9,10,14,17). The agents showed poor activity against G. vaginalis and U. urealyticum.…”
mentioning
confidence: 59%
“…We found most U. urealyticum strains tested to be resistant to the quinolones. Although lower MICs of ciprofloxacin against U. urealyticum have been reported (14), similar MIC ranges have also been documented (1,8,17).…”
mentioning
confidence: 92%
“…hominis may be inhibited by theoretically attainable concentrations of ciprofloxacin according to a number of studies (14,17,19,26,27,39,46). MICs for other quinolones have also been reported (17,19,20,26,27,33,39,41,46 (1,2,7,15,17,19,26,27,33,39,46).…”
Section: Discussionmentioning
confidence: 99%